Mathematics for decision making : - Martin, E. Wainright (R. D. Irwin, 1969)
This is a marvelous book. It deals with serious mathematics, but it is a self-teaching tool. It begins with the most basic of basics to make sure that the reader is ready for more and then continues into more advanced topics. It is so well constructed that all the reader needs is an understanding of the most basic logic.